PENGARUH PEMBERDAYAAN APARATUR TERHADAP EFEKTIVITAS PELAYAN PUBLIK PADA KANTOR DESA OMAYUWA KECAMATAN RANDANGAN KABUPATEN POHUWATO - Gretty Syatriani Saleh (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
The purpose of this study was to determine the effect of Apparatus Empowerment on the Effectiveness of Public Servants at the Omayuwa Village Office, Randangan District, Pohuwato Regency. The method in this research is descriptive analysis with quantitative and qualitative approaches, namely research that uses numbers and words or sentences and pictures by using samples and using questionnaires. The results showed that the Effect of Apparatus Empowerment on the Effectiveness of Public Servants at the Omayuwa Village Office, Randangan District, Pohuwato Regency, the authors can conclude that simultaneously, apparatus empowerment in the form of development, coaching, and payroll have a positive and significant effect on the effectiveness of public services at the Omayuwa Village Office, Randangan District. Pohuwato Regency, with the number of coefficients of multiple determination (R2y,x1,x2,x3,) of 0.611 (61.1%). while 0.389 (38.9%) is determined by other variables not examined. Based on the results of the significance test, it was found that the sig value (0.037) is greater than the alpha value (0.05), so the effect is positive and significant. Partially, coaching has an effect on the effectiveness of public services by 0.233 (23.3%). Based on the results of the significance test, it was found that the sig value (0.021) was greater than the alpha value (0.05), so the effect was significant. coaching has an effect on the effectiveness of public services by 0.227 (22.7%). Based on the results of the significance test, it was found that the sig value (0.019) was greater than the alpha value (0.05), so the effect was significant. Education and training affect the effectiveness of public services by 0.186 (18.6%). Based on the results of the significance test, it was found that the sig value (0.016) was greater than the alpha value (0.05), so the effect was significant.